Assessment of Various Risk Factors for Biological and Mechanical/Technical Complications in Fixed Implant Prosthetic Therapy: A Retrospective Study - Dimitrios Bardis; Doriana Agop-Forna; Stavros Pelekanos; Nicolae Chele; Cristina Dascălu; Roland Török; Bianca Török; Ioana Cristea; Panagiota Moulavasili Bardi; Norina Forna (Diagnostics, 2023)
The goals of this research were to determine the influence of several factors on implants’ biological and technical complications in posterior fixed implant prosthetic therapy. Materials and methods: The study group consisted of 67 edentulous patients (mean age: 63.88 ± 11.709 yrs; 20 males, 47 females) with implant prosthetic therapy for posterior edentulism. A total of 76 implant-supported fixed partial dentures (IP-FPDs) and 178 implants were assessed using clinical and paraclinical assessments. Risk factors for biological complications (peri-implantitis) and technical complications were determined by using the Pearson Chi-squared test and multivariate analysis. Results: The implant success (the absence of biological and mechanical/technical complications) was 66.30%. The prevalence of biological complications was 13.5%. The prevalence of technical complications was 28.70%. Variables that were associated with a higher risk of peri-implantitis were poor oral hygiene and bruxism. In univariate analysis, poor oral hygiene increased the risk of peri-implantitis 5.778 times and bruxism 5.875 times. Variables that were associated with a higher risk of mechanical/technical complications were age group > 60 yrs, smoking, history of periodontal disease, and bruxism. In univariate analysis, the risk of technical complications increased 4.14 times for patients in the age group > 60 years (vs. age group 40–60 years) and 20.5 times for patients with bruxism. Bruxism and smoking were significant predictors of mechanical/technical complications in the multivariate model. Conclusions: In univariate models, patients with poor oral hygiene and bruxism have an increased risk of peri-implantitis. In multivariate models, we did not identify significant predictors of peri-implantitis. Age group > 60 yrs, smoking, history of periodontal disease, bone grafting, and bruxism are risk factors for the increase in the mechanical/technical complication rate. In the multivariate model, smoking and bruxism are significant predictors of the mechanical/technical complications.